Geochemical reactions altering the mineralogical and multiscale pore characteristics of uranium-bearing reservoirs during CO2 + O2in situ leaching - Zhou, Xingyu; Wang, Wei; Niu, Qinghe; Wang, Qizhi; Su, Xuebin; Zhou, Genmao; Zhao, Lixin; Ji, Zhongmin; Qi, Xiaofei; Tian, Lanlan; Zhang, Jianhui; Sun, Beibei (Frontiers in Earth Science, 2023)
The CO2+O2 in-situ leaching has been extensively applied in the uranium recovery in sandstone-type uranium deposits of China. The geochemical processes impact and constraint the leaching reaction and leaching solution migration, thus it is necessary to study the CO2+O2-water-rock geochemical reaction process and its influence on the physical properties of uranium-bearing reservoirs. In this work, X-ray diffraction (XRD) and high-pressure mercury intrusion porosimetry (HPMIP) were employed to analyze the mineralogical and multiscale pore characteristics of typical samples. Results show that the CO2+O2-water-rock geochemical reaction has complicated effects on the mineral compositions due to the various reaction modes and types. After the CO2+O2-water-rock geochemical reaction, the femic minerals decrease and the clay minerals in the coarse sandstone, medium sandstone, fine sandstone and siltstone increase, while the femic mineral and clay mineral in sandy mudstone show the contrary changing trend. The CO2+O2-water-rock geochemical reaction decreases the total pore volume of uranium-bearing reservoirs, and then promotes pores transformation from small scale to large scale. The fractal dimensions of macropore are decreased, and the fractal dimensions of mesopore, transition pore and micropore are increased. The effects of felsic mineral and carbonate dissolution, secondary mineral precipitate, clay mineral swelling and mineral particle migration simultaneously present in the CO2+O2 in-situ leaching process, which exhibit the positive transformation and the negative transformation for the uranium-bearing reservoirs. The mineral dissolution may improve reservoir permeability to a certain degree, while the siltation effect will gradually reveal with the extension of CO2+O2 in-situ leaching. This research will provide a deep understanding of the physical property response of uranium-bearing reservoirs during CO2+O2 in-situ leaching, and indicate the direction for the efficient recovery of uranium resources.